Examining Drivers of Health Care Spending: Evidence on Self-referral Among a Privately Insured Population. Issue 7 (July 2017) - Mitchell, Jean M.; Reschovsky, James D.; Film, Roy J.; Franzini, Luisa
Abstract : Background: Despite the enactment of laws to restrict the practice of self-referral, exceptions in these prohibitions have enabled these arrangements to persist and proliferate. Most research documenting the effects of self-referral arrangements analyzed claims records from Medicare beneficiaries. Empirical evidence documenting the effects of self-referral on use of services and spending incurred by persons with private insurance is sparse. Objectives: We analyzed health insurance claims records from a large private insurer in Texas to evaluate the effects of physician self-referral arrangements involving physical therapy on the treatment of patients with frozen shoulder syndrome, elbow tendinopathy or tendinitis, and patellofemoral pain syndrome. Study Design: We used regression analysis to evaluate the effects of episode self-referral status on: (1) initiation of physical therapy; (2) physical therapy visits and services for those who had at least 1 visit; and (3) total condition-related insurer allowed amounts per episode. Results: For all 3 conditions, we found that patients treated by physician owners were much more likely to be referred for a course of physical therapy when compared with patients seen by physician nonowners. A consistent pattern emerged among patients who had at least 1 physical therapy visit; non–self-referred episodes included more physical therapy visits, and more physical therapy services per episode in comparison with episodes classified as self-referral. Most self-referred episodes were short and the initial visit did not include an evaluation. Conclusion: Physician owners of physical therapy services refer significantly higher percentages of patients to physical therapy and many are equivocal cases.